Young Soldiers of Supervision: Supervision Practices in Turkey1 - Kiye, Semra (My University, 2023)
Supervision is a systematic intervention by the more experienced professional on the development of the less experienced. The aim of this research is to describe the current situation by examining the perceptions, opinions and experiences of research assistants who provide support in the supervision process in Turkey. The research was carried out as a phenomenology study, one of the qualitative research methods. The working group consisted of 12 research assistants (6 women, 6 men) working in nine universities which are located in the Eastern Anatolia Region, Central Anatolia Region and Aegean Region of Turkey. Demographic Information Form and Semi-Structured Interview Form were used in the interviews. Descriptive analysis technique was used in the analysis of the data. According to the findings, three main themes were reached. These main themes were named as views on receiving supervision, views on giving supervision, and views on being a supervisor. As a result, it was determined that most of the participants received supervision during the training processes, but half of the group did not have any training on being a supervisor.